Nitrous oxide production from an ultisol of the humid tropics treated with different nitrogen sources and moisture regimes - M., Khalil; A., Rosenani; Cleemput, O. Van; P., Boeckx; J., Shamshuddin; C., Fauziah (Springer, 2002)
To investigate the impact of different N sources and moisture regimes on N2O production, laboratory incubations using a Bungor series soil (Typic Paleudults) were carried out for a period of 25 days. A maximum N2O flux was detected upon application of chicken manure (2,379±221 µg N2O-N kg–1 soil day–1) at 60% water-filled pore space (WFPS). Application of KNO3, groundnut residue and urea resulted in a smaller emission rate (615–699 µg N2O-N kg–1 soil day–1). Addition of (NH4)2SO4 and maize residue produced the lowest rate, 246±40 and 229±54 µg N2O-N kg–1 soil day–1, respectively. The increase in pH H2O to around 5.5, upon addition of urea and organic matter, increased the N2O production markedly after a lag period for nitrification. The N2O production was increased by decreasing the C/N ratio of the organic N sources. The N2O-N loss was higher from inorganic N (3.5–8.5%) than from the organic N sources (1.6–6.7%), probably because of nitrate reduction during the initial period of incubation. The N2O fluxes generally were small (26.6–38.7 µg N2O-N kg–1 soil day–1) and were increased by increasing the moisture content. The relatively dry soil (20% WFPS) acted as a sink. The increases in total N2O production at 40%, 60% and 80% WFPS were 0.46, 0.58 and 0.72 mg N2O-N kg–1 soil, respectively, over the value at 20% WFPS. Results indicate that the acid soil could be a potential source of N2O if treated with urea/KNO3 and easily decomposable organic matter under favorable moisture conditions.